KARAKTERISTIK PENDONOR DARAH GAGAL PENGAMBILAN DARAH SAAT DONASI DI UTD PMI SLEMAN - Francisca Romana Sri Supadmi (Jurnal Ilmiah Cerebral Medika, 2020)
The need for blood in Sleman Regency is around 1.000 bags blood every month. Meanwhile, the blood production at Indonesian Red Cross Blood Transfusion Service Sleman Regency is around 11.500 blood bags not to mention reduced by the blood bags that must be destroyed around 1.500 blood bags, one of the causes is due to failed to blood draw. Blood donors who failed to blood draw were then recorded at blood donor management information system (SIMDONDAR) Indonesian Red Cross Blood Transfusion Service Sleman Regency, and then classified according to the characteristics of blood donors. This study aims to determine the characteristics of blood donors who failed to blood draw based on gender, age, blood type, and number of blood donors at Indonesian Red Cross Blood Transfusion Service Sleman Regency in 2019. This research is a non-experimental quantitative study with a retrospective approach to create an objective description by looking at previously documented data. The sample in this study were 146 blood donors who failed to blood draw at Indonesian Red Cross Blood Transfusion Service Sleman Regency in 2019. Sampling using total sampling technique. There were 146 (1,27%) blood donors who failed to blood draw at Indonesian Red Cross Blood Transfusion Service Sleman Regency in 2019. The group that had the highest number of blood donors who failed to blood draw was male blood donors (55,63%), blood donors in late adolescence aged 17-25 years (47,18%), blood donors with blood group B rhesus positive (35,92%) and regularly blood donors (51,41%). The characteristics of blood donors who failed to blood draw were dominated by male blood donors, aged 17-25 years, blood group B rhesus positive and regularly blood donors.